Kategeet en geloofsvorming: Perspektiewe vanuit die Praktiese Teologie - Venter, Casper J. H. (HTS teologiese studies, 2011)
Scrutinising this topic is an attempt to equip catechists more extensively in serving and furthering the forming of faith in the process of formal catechesis given to children. An additional aim is to highlight an outcome indicated in certain practical-theological studies, that is, that the rational dimension in the forming of faith should not be accentuated one-sidedly in formal catechetical ministry within faith communities. On basis-theoretical level the following aspects are investigated: a closer definition of faith from Hebrews focusing on the forming of faith by means of catechesis; the action of learning in the forming of faith; the sequence in the action of teaching as indicated in Scripture; the gifts of the Holy Spirit in intermediating the process of forming faith; the way and attitude in which the catechist fulfils his or her ministry, and in last instance, the spirituality of the catechist. On metatheoretical level applicable aspects from the field of Emotional and Social Intelligence are investigated. Data from the field of Emotional Intelligence that should be part of the catechist’s teaching equipment point to the necessity of being conscious of aspects such as self-awareness, self-control, self-motivation and social skills. Contributions from the field of Social Intelligence include attitudes and skills like empathy, the ability of presenting oneself effectively in formulating ideas, the authority with which the catechist communicates, and his or her caring for someone else’s needs. In final instance, relevant practice-theoretical perspectives that can be applied in catechetical ministry, and specifically in the forming and passing on of faith, are outlined.